Diagnostic Accuracy of Magnetic Resonance Imaging in Detecting Perianal Fistula, Taking Surgical Findings as Gold Standard - Sikander, Mishal; Alia, Nayab; Nazir, Muhammad Hassan; Liaquat, Fatimah (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the diagnostic accuracy of magnetic resonance imaging in detecting perianal fistula, taking surgical findings as gold standard. Study design: Cross-sectional (validation) study. Settings: Department of Radiology, Madinah Teaching Hospital, Faisalabad. Study Duration: 15th June 2024 to 14th December 2024. Methodology: The study comprised 140 patients aged 18 to 70 years presenting with complaints of perianal discharge with or without perianal pain. Patients who had surgery for perianal fistula, history of perianal fistulectomy, cardiac pacemakers and indwelling metallic stents were excluded. After that, MRIs were taken of each patient using a 1.5 T MR scanner. A phased-array coil was employed in all methods to capture images under all conditions. The distal rectum, anal canal, and subcutaneous tissues were all included in the imaging volume. Images of fat saturation were captured in the coronal, oblique, and axial planes. A radiologist examined the pictures and noted whether or not there was a perianal fistula. After that, the patients had surgery, and the results were recorded. Operative and MRI results were contrasted. Results: The peri-anal fistula was detected by MRI with sensitivity of 92.86%, specificity of 85.71%, PPV of 90.70%, NPV of 88.89%, and diagnostic accuracy of 90.0%. Conclusion: According to the study's findings, MRI is an extremely sensitive and precise imaging technique for pre-operative evaluation of peri-anal fistula.